DEVELOPMENT OF INQUIRY-BASED LEARNING ENVIRONMENT SCALE: A VALIDITY AND RELIABILITY STUDY - Ayberk Bostan Sarıoğlan (MOJES: Malaysian Online Journal of Educational Sciences, 2021)
Researchers have studied the effects of using inquiry-based teaching in science lessons on students' learning for many years. Based on this, the purpose of this study is to develop an inquiry-based learning environment scale for middle school science classes and to conduct validity and reliability analyses. The Inquiry-Based Learning Environment Scale (IBLES) was first created with 63 items based on literature review. The scale, which was finalized after taking expert opinions, includes 37 items in total. The scale was applied to 765 students, including 364 female and 401 male students, studying at a middle school. First, Kaiser-Meyer-Olkin and Bartlett Sphericity tests were conducted for the suitability of the data for factor analysis. The results obtained showed that the data were suitable for factor analysis. Then, exploratory factor analysis was carried out. As a result of the factor analysis, six items were removed from the scale, the remaining 31 items were gathered under seven factors, and the items under these factors were established. Confirmatory factor analysis of the scale was carried out with the LISREL program, and it was found that the model's compliance level with the data was good. Cronbach's alpha reliability coefficient of the whole scale was calculated to be .815 in the reliability analysis of the IBLES. The internal consistency coefficients of the items in each factor and the relationship between the factors were calculated using the Pearson Correlation coefficient. As a result, it was found that this scale has a sufficient level of validity and reliability that it can also be used in other studies to evaluate the learning environment of middle school students.